First-principles study of O3 molecule adsorption on pristine, N, Ga-doped and -Ga-N- co-doped graphene - Beall, G.W.; Akhmetsadyk, D.S.; Ilyin, A.M.; Tulegenova, M.A. (Karagandy University of the name of acad. E.A. Buketov, 2024)
The adsorption of O3 molecules (ozone) on graphene, N-doped graphene, Ga-doped graphene, and -Ga-N- co-doped graphene with an emphasis on O3 detection was examined in this work. The physical characteristics of -Ga-N-co-doped graphene are significantly altered upon O3 adsorption, which makes it a suitable choice for O3 detection molecular sensors. The interaction between the O3 molecule and the adsorbent is explained on the basis of their adsorption energy, adsorption distance and charge transfer. It was found that the adsorption of ozone molecules on the -Ga-N- co-doped graphene was more favorable in energy than that on the pristine one, representing the superior sensing performance of -Ga-N- co-doped system. In our work, we estimated the charge transfer between the O3 molecule and doped graphene nanostructures based on Mulliken population analysis. The calculated adsorption energy value shows the ozone molecule more firmly adsorbs on the surface of -Ga-N- co-doped graphene nanostructures (Eads = –1.74 eV) than that of pristine graphene (Eads = –0.41 eV), deriving from a stronger covalent bond between the ozone molecule and the -Ga- N- co-doped graphene nanostructures. Our findings thus suggest that -Ga-N- co-doped graphene could be a highly efficient gas sensor device for O3 detection in the environment.
Таза графенде, N, Ga және -Ga-N- қoса легирленген графенде O3 молекуласының адсорбциясының алғашқы принциптерін зерттеу
Исследование первых принципов адсорбции молекулы O3 на чистом графене, легированном N, Ga, и -Ga-N- co-легированном графене
Keywords: graphene; O3 adsorption; density functional theory; N-doped graphene; Ga-doped graphene; gas sensor; graphene-based sensors